2001
DOI: 10.1007/s005350170096
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis in the elderly: clinical patterns and outcome in 51 Greek patients

Abstract: It is concluded that ulcerative colitis in elderly Greek patients runs a rather similar course to that in younger patients. However, some unique characteristics observed in the elderly patients (lower rate of colectomy, absence of patients with colorectal cancer, and increased death rate) could be attributed either to truly different disease behavior in the elderly people or to factors directly related to their advanced age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 13 publications
(10 reference statements)
2
20
1
2
Order By: Relevance
“…In contrast to our findings, a retrospective study from Greece by Triantafillidis et al [17] found no difference in UC disease extent by age of diagnosis. Fifty-one (12%) patients were diagnosed after age 60, while 362 were diagnosed prior to age 60.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, a retrospective study from Greece by Triantafillidis et al [17] found no difference in UC disease extent by age of diagnosis. Fifty-one (12%) patients were diagnosed after age 60, while 362 were diagnosed prior to age 60.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, among the elderly a notably lower severity index was found, suggesting a decline in severity in this population as interpreted from the decrease in number of exacerbations, regression in extension of the inflammatory lesions, colectomy requirements, and risk of colorectal cancer as previously reported. [38][39][40] This evidence could be helpful for future classification of UC, indicating that a more meaningful age division may be set at 60 years, stratifying patients above this age as elderly colitis. This observation was previously found in the IBSEN study, 28 suggesting that the course of UC becomes milder with increasing age, and that the initial age should be detached from the clinical classification of patients.…”
Section: Discussionmentioning
confidence: 96%
“…[25][26][27] Data on the disease course of EO IBD are mainly derived from small selected referral center cohorts, some collected decades ago. [28][29][30][31][32][33][34][35][36][37][38][39] Recent population-based data from the Hungarian registry and the French EPIMAD registry suggested a somewhat milder course of IBD diagnosed at older age, yet the number of elderly patients was limited 40 or data from the corresponding adult population were lacking, 41 impeding a direct comparison. To balance benefit and risk of treatment strategies in the elderly population, information on the current treatment strategy and disease outcome is needed, preferably from a large unselected population of patients with IBD studied in direct comparison to AO disease.…”
mentioning
confidence: 99%